2009
DOI: 10.3389/neuro.19.001.2009
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced long term microcircuit plasticity in the valproic acid animal model of autism

Abstract: A single intra-peritoneal injection of valproic acid (VPA) on embryonic day (ED) 11.5 to pregnant rats has been shown to produce severe autistic-like symptoms in the offspring. Previous studies showed that the microcircuitry is hyperreactive due to hyperconnectivity of glutamatergic synapses and hyperplastic due to over-expression of NMDA receptors. These changes were restricted to the dimensions of a minicolumn (<50 μm). In the present study, we explored whether Long Term Microcircuit Plasticity (LTMP) was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 68 publications
(92 reference statements)
1
27
0
1
Order By: Relevance
“…to GW 23–26 in humans), even before thalamocortical synapses are established and before the critical period for thalamocortical plasticity in A1 (Barkat et al, 2011). Our findings are also consistent with general excitatory hyperconnectivity in other cell types and brain regions at older ages in the VPA model (Markram et al, 2007; Rinaldi et al, 2008a; Rinaldi et al, 2008b; Silva et al, 2009). However, the LSPS technique that we employed allowed us to investigate circuit structure on the ‘mesoscale’ (~100 μm), and sample a larger area (~1 mm 2 ) than previous studies.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…to GW 23–26 in humans), even before thalamocortical synapses are established and before the critical period for thalamocortical plasticity in A1 (Barkat et al, 2011). Our findings are also consistent with general excitatory hyperconnectivity in other cell types and brain regions at older ages in the VPA model (Markram et al, 2007; Rinaldi et al, 2008a; Rinaldi et al, 2008b; Silva et al, 2009). However, the LSPS technique that we employed allowed us to investigate circuit structure on the ‘mesoscale’ (~100 μm), and sample a larger area (~1 mm 2 ) than previous studies.…”
Section: Discussionsupporting
confidence: 87%
“…1A–B). In utero exposure to VPA has been associated with hyperconnectivity in different cortical areas (Markram et al, 2007; Rinaldi et al, 2008a; Rinaldi et al, 2008b; Silva et al, 2009). To test if SPNs received increased excitatory input we performed whole-cell patch recordings of miniature excitatory post-synaptic potentials (mEPSCs) from A1 SPNs in acute TC slices.…”
Section: Resultsmentioning
confidence: 99%
“…However, STDP does mold synaptic weights (47), and long-term microcircuit plasticity (LTMP) does mold the connectivity between these pyramidal neurons (45,66) in this same preparation. The specific neurons involved in a group may, therefore, be selected by experience, but because of the powerful connectivity constraints that we found, these forms of plasticity is likely to add only minor variations to functioning of neuronal groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in our lab demonstrated that the neocortex and amygdala of VPA-treated rat offspring is hyper-reactive and hyper-plastic due to hyper-connectivity between neurons (Rinaldi et al, 2007; Markram et al, 2008; Rinaldi et al, 2008a,b; Silva et al, 2009). These observations indicate excessive processing and storage of information in these nervous systems.…”
Section: Introductionmentioning
confidence: 97%